The Importance Of Non-Musical Elements And Level Of Satisfaction In A Live Musical Show - Mohd Fahmi, Bin Yahaya; Lee, Ying Quan; Nordiana, Ahmad Nordin (Publications International Lahore, 2017)
This study examines the importance of non-musical elements in a live musical performance focusing primarily on musical environment, musician, physical setting and audience interaction. It also analyses audience levels of satisfaction on each one of the variables involve. The construct was developed based on present literature and was put to the test on Malaysian grounds. A set of 200 self-administered questionnaires were randomly distributed to audiences at several musical performance venues. The data was analysed quantitatively using descriptive statistics. Due to the experiential nature of performing arts, it is to the best interest of production crew as well as the artists involved to know what is it that audiences look for in a live musical performance and serve them. The evidence from this study suggested that audience response to musical as well as non-musical elements. In order to ensure delightful experience, arts event managers are advice to give if not equal, considerable attention to the factors involved.